1994
DOI: 10.1007/bf00417687
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral function in diabetes mellitus

Abstract: Diabetes mellitus is a common metabolic disorder associated with chronic complications such as nephropathy, angiopathy, retinopathy and peripheral neuropathy. Diabetes is not often considered to have deleterious effects on the brain. However, long-term diabetes results in a variety of subtle cerebral disorders, which occur more frequently than is commonly believed. Diabetic cerebral disorders have been demonstrated at a neurochemical, electrophysiological, structural and cognitive level; however, the pathogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
158
2
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 302 publications
(161 citation statements)
references
References 107 publications
0
158
2
1
Order By: Relevance
“…Studies using magnetic resonance imaging techniques have identified abnormal white matter structure and function as well as reduced gray matter volume and density in diabetic patients [8,9]. All these abnormalities are closely related to brain metabolic disorders [10]. For example, decreased N-acetyl aspartate (NAA) [11] and increased myo-inositol (m-Ins) [12] concentrations have been observed in the white matter of individuals with diabetes by using localized proton nuclear magnetic resonance ( 1 H NMR).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using magnetic resonance imaging techniques have identified abnormal white matter structure and function as well as reduced gray matter volume and density in diabetic patients [8,9]. All these abnormalities are closely related to brain metabolic disorders [10]. For example, decreased N-acetyl aspartate (NAA) [11] and increased myo-inositol (m-Ins) [12] concentrations have been observed in the white matter of individuals with diabetes by using localized proton nuclear magnetic resonance ( 1 H NMR).…”
Section: Introductionmentioning
confidence: 99%
“…Decreased glutamine (Gln) supply to gamma-aminobutyric acid (GABA)ergic neurons has been observed in the cortex and subcortex of young epileptic rats, whereas astrocytic metabolism has been increased in adult epileptic rats [22]. Mason et al applied [2][3][4][5][6][7][8][9][10][11][12][13] C]acetate as a tracer to evaluate the hypothesis that patients with type 1 diabetes exhibit increased blood-brain transport and monocarboxylic acid (MCA) metabolism to sustain upregulated MCA transporters during hypoglycemia [23]. 13 C MRS is a primary technique for studying brain metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Nondiabetic control mice preferred the exploration of the object placed in a novel location while the diabetic mice did not, indicating impaired spatial object-placement memory. This mild disturbance is typically observed at early stages of diabetes, while during a more prolonged disease state more severe behavioral deficits were established [76,77].…”
Section: Normalization Of Hippocampal Alterations During Diabetes Melmentioning
confidence: 95%
“…Hence, remodeling of the structure of the hippocampus is accelerated and its vulnerability to cognitive dysfunctions is enhanced during diabetes in a process that can be blocked by antiglucocorticoid therapy. Previously, hyperglycemia and insulin deficiency were thought to underlie the hippocampal deficits (see [76,77] for reviews), but these possibilities can be excluded in view of the experiments of Revsin et al [75,78], although synergy between these conditions and the deleterious effect of hypercortisolemia cannot be ruled out. A rationale behind this observation is that the blockade of the GR would allow a more prominent function of neuroprotective MR-mediated actions [9].…”
Section: Normalization Of Hippocampal Alterations During Diabetes Melmentioning
confidence: 99%
See 1 more Smart Citation